“Doing College” Amidst COVID-19: A Comparative Study Exploring Differences in the Psychological Experiences of International and Domestic Students in the U.S. - Paul, Narmada; Han, Jaeyun; Usher, Ellen L. (Journal of International Students, 2023)
Mindset beliefs (beliefs about malleability of human attributes) likely influenced the psychological adjustment of undergraduate students during the pandemic. This study investigated the role of mindset beliefs about adaptability (the ability to adapt to change) in shaping the mental health and behavioral engagement of international and domestic students in the U.S. The psychological experiences of 98 international students and 98 domestic counterparts enrolled at a public U.S. institution during Fall 2020 were compared. Tests of mean differences showed that, relative to domestic students, international students reported a stronger belief that people could become more adaptable to changing circumstances. International students also reported better mental health. The two groups did not differ in their academic behavioral engagement. Path analysis showed that mental health mediated the relationship between international student status and behavioral engagement, whereas mindset beliefs about adaptability did not. The findings highlight the psychological strengths of international students.